Antioxidant Property of Aerial Parts and Root of Phyllanthus fraternus Webster, an Important Medicinal Plant - Richa Upadhyay; Jitendra Kumar Chaurasia; Kavindra Nath Tiwari; Karuna Singh (The Scientific World Journal)
In present study free radical scavenging potential of aerial parts and root of Phyllanthus fraternus was investigated. Extraction was done in water and ethanol. Total antioxidant capacity was measured by DPPH free radical scavenging method; ethanolic extract of aerial part was most potent in activity with 50% inhibition at 258 μg/mL concentration. Lipid peroxidation (LPO) was measured in terms of thiobarbituric acid-reactive substances (TBARS) by using egg-yolk homogenates as lipid-rich media with EC50 of aerial part (ethanolic) 1522 μg/mL which was found to be most active. Superoxide (SO) radical scavenging activity was measured using riboflavin-light-nitroblue tetrazolium assay. Ethanolic and aqueous extract of both aerial part and root was almost similar in superoxide radical scavenging activity. Reducing power was determined on the basis of Fe3+-Fe2+ transformation in the presence of extract. Total phenolic and flavonoid contents were also measured by spectroscopic method. Results showed that the ethanolic fraction of aerial part is most active towards antioxidant potential and this activity is related to its polyphenolic content and reducing potential. Thus, P. fraternus extract can be used as potent natural antioxidant.